The effect of covering with black plastic, and two herbicides, on the growth of weeds, and the yield of capsicum crop, in Al-Ghab area - طباش سمير; سمرة بديع; جريش أروى (Latakia University Journal -Biological Sciences Series, 2021)
The research was carried out in the Al-Ghab area during the 2019-2020 agricultural season to study the effect of mulching with black plastic (mulch), herbicides (Trifluralin and Haloxyfop), and hand weeding, on the germination and growth of weeds accompanying the capsicum crop, and its productivity compared to the non-weedy control, in a field experiment designed Completely randomized sectors, with four replications, after 30, 60 and 90 days of cultivation. The results showed the prevalence of nine types of weeds, including six broad-leaved and three thin-leaved. The results showed that the black plastic mulching treatment was superior to all treatments, as it prevented the development of weeds from the beginning of planting, followed by the manual weeding treatment. The treatment with Trifluralin achieved control of weeds, especially after 30 days. The effectiveness of the herbicide Haloxyfob did not appear clearly because it is specialized in combating thin-leaved weeds. which were present in a small percentage. The treatments of mulching and manual weeding also showed superiority in increasing the number of branches of pepper plants and increasing fruit production compared to other treatments. Hand weeding and black plastic mulching treatment achieved the best yield with increase of 241,7% and 232.15 % in a row for the non- grassed.